Tribute to My Jan (Comparative & International Education Series, 2022)
“Jan is no more,” said Jan’s husband. I was getting ready to start work when I received the call on 24 September 2014. I could not take it in and I cannot recall what I said to Jan’s husband. All the flashes of memories, our conversations and laughter rushed in. “How can that be?” I told myself; I just met her a few months ago. I knew she was very sick but never thought she would go that soon.